274 ASSESSMENT OF THE ANTI-PROLIFERATIVE EFFECTS OF STANDARD CHEMOTHERAPY AND PAN-HER FAMILY TYROSINE KINASE INHIBITORS IN ESOPHAGEAL CANCER CELL LINE MODELS. (14th September 2020) - Al Azzawi, M; Gaynor, N; Crown, J; Collins, D; Robb, W
Abstract:  : Esophageal cancer is the 9th most common cause of cancer globally with a mortality:incidence ratio of 0.88 and a 5 year mortality rate of 19%. Herceptin, a HER2 targeted monoclonal antibody, is approved for use in metastatic HER2+ gastroesophageal carcinoma. To further examine the benefits of HER family inhibition in esophageal cancer, the effects of pan-HER family TKIs and standard chemotherapy in HER2+ and HER2-low cell line models were examined. Methods: Two cell lines, OE19 (HER2+) and FLO-1 (HER2-low) were used to examine the effect of the standard FLOT chemotherapy regimen (5 flurouracil (5FU), oxaliplatin and docetaxel) and pan-HER TKIs neratinib and poziotinib. All compounds were from commercial sources. 2D acid phosphatase-based proliferation assays were utilised to assess the anti-proliferative effects of these agents. Triplicates of each assay were performed and standard deviations were determined. IC50 values were calculated using Calcusyn ® software. Results: The OE19 cell line demonstrated a high sensitivity to neratinib and poziotinib with IC50 values of 3.426+/−0.187 nM and 0.307 +/−0.051 nM), respectively. IC50 values for neratinib (0.147+/−0.080 μM) and poziotinib (2.4+/−0.471 μM) were significantly higher (p < 0.05) in the FLO-1 cell line compared to OE19. The IC50 values for oxaliplatin and docetaxel were comparable between the OE19 and FLO-1. However, both cell lines were insensitive to 5FU with IC50 values greater than 10 μM. Conclusion: The HER2+ cell line was significantly more sensitive to the pan-HER family TKIs neratinib and poziotinib, compared to the HER2-low cell line. This may indicate a potential use for pan-HER family TKIs in HER2+ esophageal cancer. Further work is being conducted to assess potential synergy between pan-HER family TKIs and chemotherapy in these models.